Impact of Reliance JIO on Indian Telecom Industry: An Empirical Study - Singh, Rajbinder (International Journal of Scientific Research and Management (IJSRM), 2017)
Telecommunication industry is one of the most emergent industries which face evolved very speedily in last decade. Currently India is the world’s second largest telecommunication market and still growing. Mobile economy in India is increasing very fast and will add significantly to India’s GDP. Indian telecommunication market is a excellent opportunity for network providers from native and exogenous Players. Both Indian network providers’ international providers receive considerable market share in the Indian mobile industry. Recently Reliance Jio has gave a big jolt to Indian telecom industry, schemes like free internet, free calling, 4g network provide a serious threat to others. Reliance Jio emerge a new choice and other service providers face a new kind of challenge and find difficult to cope up with new circumstances. This research paper discusses the features of the jio and also through some light on the competitive edge over other service providers.